Purification and properties of branched-chain alpha-keto acid dehydrogenase phosphatase from bovine kidney. - Damuni, Z (1984)
Branched-chain alpha-keto acid dehydrogenase (BCKDH) phosphatase was purified about 8000-fold from extracts of bovine kidney mitochondria. The highly purified phosphatase exhibited a molecular weight of approximately 460,000, as estimated by gel-permeation chromatography. Another form of the phosphatase, with an apparent molecular weight of approximately 230,000, was also detected under conditions of high dilution. In contrast to pyruvate dehydrogenase phosphatase, BCKDH phosphatase was active in the absence of divalent cations. BCKDH phosphatase was inactive toward 32P-labeled phosphorylase a, but exhibited approximately 10% maximal activity with 32P-labeled pyruvate dehydrogenase complex. BCKDH phosphatase activity was inhibited by GTP, GDP, ATP, ADP, UTP, UDP, CTP, and CDP. Half-maximal inhibition occurred at about 60, 200, 200, 400, 100, 250, 250, and 400 microM, respectively. These inhibitions were reversed completely by 2 mM Mg2+. GTP was replaceable by guanosine 5'-(beta, gamma-imido)triphosphate. GMP, AMP, UMP, CMP, NAD, and NADH showed little effect, if any, on BCKDH phosphatase activity at concentrations up to 1 mM. Heparin showed half-maximal inhibition at 2 micrograms/ml. This inhibition was only partially (30%) reversed by 2 mM Mg2+. CoA and various acyl-CoA compounds exhibited half-maximal inhibition at 150-300 microM. These inhibitions were not reversed by 2 mM Mg2+. BCKDH phosphatase activity was stimulated 1.5- to 3-fold by protamine, poly(L-lysine), and poly(L-arginine) at 3.6 micrograms/ml.